Ethical leadership: theory, practice & implication - Salleh, Mohamad Johdi; Tiyunin, Zenita Arryani (Institut Terjemahan & Buku Malaysia (IBKM) and International Islamic University Malaysia (IIUM)., 2016)
Leaders can be perceived as someone who have power in the society and must ensure that they are practising ethics in every actions and conducts that they are performing as it will not only influence their subordinates to be equally ethical but it will also generate on ethical environment in an organization. This society perceived the organization as can be trusted and they will look up to the organization when the leaders act ethically while conducting their daily duties. As such, it shows how important ethics can be in an organization.